Development of a Web-Based Information Sharing System for Chronic Disease Patient in Palestinian Ministry of Health - Alqrinawi, Suhail S. M. (2011)
Sharing information between organization and companies plays important roles in achieving good perfiormance. When the organization or companies want to share any type of data especially the personal and health information, such information or data are availabe in the hospital for sharing. The information sharing has categories like the data maintainance for privacy, value and validity. This study focuses on investigating the existing approach of sharing and retrieving patient information and to develop prototype to make electronic health record more easy to access. A web-application prototype was developed using ASP.NET SQL Server2005 for sharing patients' information. Finally, the users' satisfaction of the developed prototype was measured using IBM Computer Usability Satisfaction Questionnaires.